Synthesis, biological activity and physicochemical properties evaluation of antiplasmodial pyrimido[1,2-a]benzimidazoles - Disraeli, Chiara (Department of Chemistry, 2023)
Malaria is an infectious disease which still causes high morbidity and mortality rates among the world's poorest populations, especially in tropical and sub-tropical regions. In 2020, 241 million malaria cases and 627 000 associated deaths were reported, with 94% of them on the African continent, according to the World Health Organization (WHO). The emergence of drug resistant strains of Plasmodium falciparum, the causative agent of the vast majority of malaria cases, has prompted the urgent need to develop new antimalarial drugs with novel modes of action and no cross resistance to existing medicines. Pyrido[1,2-a]benzimidazole (PBI) derivatives have been previously identified as antimalarial compounds with promising in vitro activity against Plasmodium falciparum and in vivo antimalarial efficacy. Unfortunately these compounds are beset by poor aqueous solubility and suboptimal in vivo pharmacokinetics (PK), which present barriers to in vivo efficacy improvement. Towards addressing these issues through improved physicochemical properties, in particular solubility, the related pyrimido[1,2-a]benzimidazole scaffold has been investigated within the context of this dissertation. A new series of compounds was designed and synthesized to expand the structureactivity relationship (SAR) scope and improve physicochemical properties, including aqueous solubility. To this end, the study was broadly diversified into three SAR series (SAR1, SAR2 and SAR3). In SAR1, various aliphatic amine side chains were explored. SAR2 analogues aimed at disrupting molecular planarity by increasing the dihedral angle and thereby potentially enhancing solubility through minimising intermolecular π-π stacking interactions. The design of SAR3 compounds was aimed at incorporating representative diverse lipophilic (π) and electronic (σ) Craig plot substituents and/or low molecular weight amide substituents in the C-3 position of the phenyl ring. Thirty-eight (38) derivatives were synthesized, characterised and their in vitro asexual blood and gametocytocidal antiplasmodium and cytotoxic activities evaluated. Towards assessing the potential of the compounds to target the host hemoglobin degradation pathway in an analogous manner to the related PBI derivatives, compounds were also evaluated in the synthetic hemozoin, beta-hematin inhibition (βHIA) assay. Aqueous solubility, and for selected compounds, microsomal metabolic stability, were also evaluated. The most potent compounds against the asexual blood stage (ABS) parasites belonged to SAR3 series with the most active derivative being 19 (IC50 (PfNF54) = 0.156 μM), which combined the electron-withdrawing properties of both p-CN and m-CF3. Its beta-hematin inhibition activity (IC50 = 16.8 μM) was comparable to the standard control drug chloroquine (IC50 = 17 μM). SAR1 compounds showed good antiplasmodium activity, although lower than SAR3 analogues. On the contrary, selected analogues showed the most favourable microsomal metabolic stability, with ≥ 75% of compound unchanged after 30 minutes of incubation. SAR2 derivatives showed low antiplasmodium activity, as well as beta-hematin inhibition activity. All compounds showed no cytotoxicity against human hepatoma HepG2 and Chinese hamster ovarian (CHO) cells, exhibiting acceptable selectivity indices (SI>10). Overall, most of the synthetized compounds showed minimal gametocytocidal activity against both early- (EG) and late- (LG) stage P. falciparum gametocytes (< 50% inhibition at both 5 μM and 1 μM), except 9 (IC50 (PfNF54) = 0.725 μM) which was highly active against the EG with an IC50 of 0.244 μM, confirming this to be a dual-acting antiplasmodium agent. Strategies adopted to improve solubility involved incorporation of hydrogen bonding donors and acceptors, the introduction of polar-ionisable or neutral polar groups, or the disruption of molecular planarity. The latter strategy was adopted in SAR2 analogues and demonstrated by Density Functional Theory (DFT) calculations and analyses of X-ray crystallographic data. However, this strategy did not improve solubility and resulted in compounds with poor ABS activity. The most improvements in kinetic solubility were obtained from introducing the hydrophilic p-CN (18: 130 μM) in the C-3 position of the phenyl ring and in SAR3 amide series (e.g. 36: 175 μM).